The Impact of Financial Management Knowledge on Entrepreneurial Intentions Among Digital Business - Hendi Yudhanto Adinugroho (Arthatama: Journal of Business Management and Accounting, 2023)
Financial management knowledge is a key determinant of entrepreneurial intentions, particularly among digital business students. A solid understanding of financial literacy enables students to identify business opportunities, assess risks, and make informed financial decisions. This study explores the relationship between financial administration knowledge and entrepreneurial aspirations through a conceptual analysis of existing literature. Findings suggest that financial literacy enhances students’ confidence, strategic thinking, and problem-solving abilities, all of which are critical for entrepreneurial success. Moreover, financial education plays a crucial role in preparing students for real-world business challenges. Individuals with strong financial management skills are better equipped to manage capital, allocate resources efficiently, and sustain business growth. Integrating financial education into entrepreneurship curricula, including business simulations, case studies, and financial technology applications, can significantly improve students' financial decision-making capabilities. Additionally, exposure to financial literacy programs, mentorship, and internships can further reinforce entrepreneurial readiness. This study highlights the necessity of embedding financial management education into digital business programs to cultivate a generation of financially competent entrepreneurs.